(untitled) (The Batuk, 2021)
Human motivation has been treated as a significant determinant of initiating work related behavior and subsequently getting optimal performance. The relationship of motivation, behavior and performance is commonly tested in several domains of human life (e.g. education, health, sports, exercise, work etc.). However, application of motivation approach in the domain of entrepreneurship is only in its infancy. Hence, this paper aims to review literature intensively that makes a clear direction for the study related to entrepreneurial motivation and suggests new research line for the future. The results found two major directions in the study of entrepreneurial motivation. The first includes the studies treating motivation as a unitary variable with partial and linking role in comprehensive framework. The second includes the studies treating motivation as multifacted construct with central role. The study helps to broaden the knowledge in the field of entrepreneurial motivation and its role to be entrepreneur.